The Effect of Microfinance Banks on Poverty Reduction in Nigeria - ONYELE, Kingsley Onyekachi; ONYEKACHI-ONYELE, Charity (Management Dynamics in the Knowledge Economy, 2020)
The nexus between microfinance banking and poverty reduction is well documented in banking and finance literature. As a poverty reduction strategy, the microfinance initiative is expected to create room for financial accessibility to the economically active poor people. Consequently, this study estimated the effect of microfinance banks’ (MFBs) on poverty reduction in Nigeria from 1992 to 2018 using the Autoregressive Distributed Lag (ARDL) approach to regression analysis. With a VAR lag order selection of two, the ARDL bounds test revealed that the poverty rate and MFBs activities were bound by a long-run relationship. The long-run estimates suggested that the MFBs loans-to-deposit ratio and liquidity ratio caused poverty reduction in the long-run. On the other hand, the short-run estimates indicated that the MFBs were unable to ensure poverty reduction within a short period, though all the variables exhibited significant coefficients within one year. These findings imply that the ability of MFBs to reduce poverty takes a long period.